Nicaragua Learning Alliance monitoring and evaluation study 2014 - Cadilhon, Jean Joseph; Landmann, Dirk (2024)
Data gathering and analysis of the impact of the structure of the Nicaragua Learning Alliance (NLA) on the conduct of its members and on achieving their capacity development objectives.